The characteristics of grape and wine production and consumption in Hungary - Monori, Lili Etelka; Turza, Brigitta Hajnalka (Acta Carolus Robertus, 2023)
The aim of this research is to provide an insight into the historical importance of grapes and wine, their impact on health, changes in wine consumption factors and their significance. Our research examines the evolution of grape and wine production in the world, the European Union and Hungary in recent decades, in the shadow of global warming, an ageing society and economic shocks. The consumption of wine as an alcoholic beverage goes back thousands of years and has a long history at international and national level. Hungary's unique and traditional wine production could also be a benchmark at international level, thanks to its famous wines, its wine regions with a long history and its uniqueness. The study uses Hungarian and international literature and secondary research databases to illustrate the evolution of international, domestic wine and grape production, consumption patterns and the current commercial situation, which, due to economic and other drastic changes, show a divergence from the past in both wine and grape production, both at domestic and international level.
Keywords: wine; influencing factors; wine production